1999
DOI: 10.1080/095851999340396
|View full text |Cite
|
Sign up to set email alerts
|

Managing human resources across cultures: a comparative analysis of practices in industrial enterprises in China and The Netherlands

Abstract: Although researchers and practitioners have come up with many good ideas for improving the employment relationship, there is no evidence for universally applicable practices. Prior theoretical work and research in the area of (intemational) human resource management indicate that cultural and contextual constraints are responsible for the problematic nature of transference of practices. This study illustrates and explains the contextual as well as cultural boundaries through a direct comparison of practices as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 25 publications
5
44
0
1
Order By: Relevance
“…Measures of variability of behavior are as readily available as measures of means and should also be reported in cross-cultural studies. The notion that organizational cultures differ on the extent to which they emphasize rules and predictability versus flexibility and experimentation has a long history in the organizational sciences (Litwin & Stringer, 1968;O'Reilly, Chatman, & Caldwell, 1991;O'Reilly & Chatman, 1996;Quinn, 1988;Rousseau, 1990 shown that flexibility and experimentation versus rule orientation is a central dimension of organizational culture (Dastmalchian, Lee, & Ng, 2000;Hofstede, Neuijen, Ohayv, & Sanders, 1990;Verberg, Drenth, Koopman, van Muijen, and Wang, 1999).…”
Section: Societal Tightness-looseness and Cross-level Effects On Indimentioning
confidence: 99%
“…Measures of variability of behavior are as readily available as measures of means and should also be reported in cross-cultural studies. The notion that organizational cultures differ on the extent to which they emphasize rules and predictability versus flexibility and experimentation has a long history in the organizational sciences (Litwin & Stringer, 1968;O'Reilly, Chatman, & Caldwell, 1991;O'Reilly & Chatman, 1996;Quinn, 1988;Rousseau, 1990 shown that flexibility and experimentation versus rule orientation is a central dimension of organizational culture (Dastmalchian, Lee, & Ng, 2000;Hofstede, Neuijen, Ohayv, & Sanders, 1990;Verberg, Drenth, Koopman, van Muijen, and Wang, 1999).…”
Section: Societal Tightness-looseness and Cross-level Effects On Indimentioning
confidence: 99%
“…For example, China is a more collectivist society than Western countries (Verburg et al, 1999). It is known that people in collectivist societies put more weight on social norms, support networks and helping each other.…”
Section: Differences In Chinese Consumer Perceptions Of Csrmentioning
confidence: 99%
“…Others identify differences between countries such as the UK and Japan (see e.g. Lam, 1994;Storey, Okasaki-Ward, Edwards, Gow, & Sisson, 1991), the UK and China (Easterby- Smith, Malina, & Yuan, 1995), China and the Netherlands (Verburg, Drenth, Koopman, Muijen, & Wang, 1999), Britain and India (Budhwar & Khatri, 2001), and the People's Republic of China and Taiwan (Warner & Zhu, 2002). And between groups of countries (Budhwar, 2000;Cheng & Brown, 1998;Tregaskis & Brewster, 2006;Wood, Brewster, & Brookes, 2014); and between the countries in Europe transitioning from communism to capitalism (Cooke, Wood, Psychogios, & Szamosi, 2011;Morley, Heraty, & Michailova, 2009;Poor, Karoliny, Alas, & Vatchkova, 2011;Sahadev & Demirbag, 2012).…”
Section: The Role Of Contextmentioning
confidence: 99%